2019
DOI: 10.1167/tvst.8.6.48
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetry in Age-Related Macular Degeneration: An Evidence-Base for Pattern Deviation Probability Analysis in Microperimetry

Abstract: Purpose: The ''traffic light'' color designation of differential light sensitivity used in a number of microperimeters does not encompass the conventional Total and Pattern Deviation probability analyses adopted by standard automated perimetry. We determined whether the color designation is indicative of abnormality as represented by the ''gold standard'' Pattern Deviation probability analysis. Methods: Total and Pattern Deviation probability levels, using two different methods, were derived at each of 40 stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, our analysis and previous studies have revealed that aging and eccentricity have a significant impact on mesopic retinal sensitivity. 17,18 Based on our findings, we predict for example that around half of the sensitivity measurements at 10° eccentricity will fall below 25 dB in healthy individuals at the age of 75.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, our analysis and previous studies have revealed that aging and eccentricity have a significant impact on mesopic retinal sensitivity. 17,18 Based on our findings, we predict for example that around half of the sensitivity measurements at 10° eccentricity will fall below 25 dB in healthy individuals at the age of 75.…”
Section: Discussionmentioning
confidence: 67%
“…6,7 To date, most work seeking to establish such normative data for microperimetry is based on separate analyses of a pre-defined test locations from standardized stimulus patterns. 17,18 One previous publication by Denniss and Astle 19 proposed using spatial interpolation to obtain normative data from specific retinal locations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported MAIA values from healthy eyes as control groups in their studies. 4,8,19,25,33 The mean MS reported ranges from 24.9 to 29.5 dB. It is important to note that direct comparing of MS values reported by different groups to our data is not appropriate as the test grids differ.…”
Section: Discussionmentioning
confidence: 71%
“…There have already been explicit attempts to replicate SAP visual field indices in retinal conditions using MP data. Pattern deviation, total deviation, mean defect, mean deviation, pattern standard deviation, and loss variance have been evaluated in recent studies [76, 180]. Cluster analysis has also been used to describe disease-specific patterns of visual field defects [180].…”
Section: Discussionmentioning
confidence: 99%
“…The S-MAIA manual states that fixation losses over 30% are unreliable. Published reports differ according to the level of fixation losses deemed tolerable, with research groups defining their own cut-offs, such as 15, 25, and 33% [74-76]. Given the small number of catch trials presented, 1 or 2 accidental button presses may be enough to classify an examination as unreliable.…”
Section: Reliability Indicesmentioning
confidence: 99%